A framework of Telemetry technology application in robotic area using MATLAB toolboxes for education - Saesar, Luhur Budi
Monitoring robot or system condition while they in operation is very important, since we do not know what is happen with our robot or our system due to far place, human limitation, our mobile activities, and etc. Nowadays we called this a Telemetry Technology. In this paper, we suggest a way to understanding Telemetry technology for education, especially on robotics field with respect to realtime data transfer. Simulink and Virtual reality toolboxes from Matlab are used to model the signal from modified joystick interface in the robot, connected to the laptop and then send the signal data through an UDP protocol using wi-fi and received by the operator laptop for data processing.